Transcranial direct current stimulation alters sensorimotor modulation during cognitive representation of movement - Bonassi, Gaia; Lagravinese, Giovanna; Putzolu, Martina; Botta, Alessandro; Bove, Marco; Pelosin, Elisa; Avanzino, Laura (Frontiers in Human Neuroscience, 2022)
We recently demonstrated, by means of short latency afferent inhibition (SAI), that before an imagined movement, during the reaction time (RT), SAI decreases only in the movement-related muscle (sensorimotor modulation) and that a correlation exists between sensorimotor modulation and motor imagery (MI) ability. Excitatory transcranial direct current stimulation (a-tDCS) on M1 could enhance the MI outcome; however, mechanisms of action are not completely known. Here, we assessed if a-tDCS on M1 prior to an MI task could affect sensorimotor modulation. Participants imagined abducting the index or little finger in response to an acoustic signal. SAI was evaluated from the first dorsal interosseus after the “go” signal, before the expected EMG activity. Participants received 20-min 1.5mA a-tDCS or sham-tDCS on M1 on two different days, in a random order. Results showed that a-tDCS on M1 increases the sensorimotor modulation consisting of a weakening of SAI after the Go signal with respect to sham-tDCS, in the movement-related muscle right before the beginning of MI. These results suggest that a-tDCS on M1 further potentiates those circuits responsible for sensorimotor modulation in the RT phase of MI. Increased sensorimotor modulation during MI may be one of the mechanisms involved in MI improvement after a-tDCS over M1.